Leader Behavior, Ability and Work Motivation in Developing Employee Productivity - Amalia, Desita Nur; Nugroho, Rusdi Hidayat (Yayasan Riset dan Pengembangan Intelektual, 2024)
The work process is influenced by various factors, such as leadership, motivation, and employee performance, all of which impact a company's productivity. At Aerofood ACS Surabaya, a decline in labor productivity has been observed, prompting the author to conduct an in-depth study on the contributing factors. This research adopts a quantitative approach to examine the effects of leadership behavior, work skills, and motivation on employee productivity at Aerofood ACS Surabaya. The data analysis revealed no issues of multicollinearity or singularity, as indicated by a determinant of the sample covariance matrix of 978.20, which is greater than zero. This fulfills the necessary assumption, strengthening confidence in the regression coefficients for each factor, as validated by the causality test. The findings indicate that leadership behavior does not have a direct impact on employability, while work motivation directly affects work efficiency. In conclusion, leadership behavior, work abilities, and motivation collectively influence productivity levels, making a significant contribution to understanding these dynamics.